Evaluation between the year of pruning and land slope on nutrient uptake and availability in tea plantation - Faris Nur Fauzi Athallah; Restu Wulansari; Aloysius Adya Pramudita (Brawijaya University, 2021)
In tea plantations, pruning to rejuvenate the plant is regularly carried out. The cutting age that is also known as pruning year determines the estimated production of tea plantations. The land slope is thought to affect the absorption of nutrients, which have implications on yields. This study aimed to explore the interaction between the pruning year and land slopes in nutrients uptake in tea plantations and to obtain the correlation between soil fertility and nutrients content in tea plants at different land slopes. A field experiment was carried out from December 2020 to February 2021 at The Research Centre for Tea and Cinchona, Gambung. A Split Plot design was conducted to observe between pruning year (PY) that consisted of pruning year 1 (PY-1), pruning year 2 (PY-2), pruning year 3 (PY-3) and pruning year 4 (PY-4) with two different slopes in each block that consisted of flat land (slope = 0-8%) and sloping land (slope = 15%-25%). Results of the study showed that there was no interaction between PY and slope on the uptake and nutrient content in the tea plant, but there was an independent effect from each factor, where the PY factor affected all nutrients uptake, while the slope factor only affected P content. There was no significant difference between flat and sloping land on soil nutrients, but there was a correlation between plant nutrients and tea plant nutrient content. P content had a strong correlation with K content (r = 0.657); and K content had a strong correlation with Mg content (r = 0.891).